Pengaruh Beban Kerja terhadap Burnout yang Dimediasi Stres Pekerjaan : Studi pada Pegawai Kantor PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan Malang - Survival Survival; Pradita Wahyuningrum; Wahju Wulandari (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of workload on burnout, with job stress as a mediating variable, on permanent employees at the Malang Customer Service Unit (UP3) of PT. PLN (Persero). This study is motivated by the increasing work demands in the public service and energy sectors, which can have an impact on increasing employee burnout. The method used in this study is quantitative, with all 180 permanent employees of PT. PLN (Persero) UP3 Malang as the population. Based on the Slovin formula, the number of samples was determined at 96 respondents. Data analysis was carried out using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of SmartPLS software. The results of the analysis show that workload has a positive and significant effect on burnout. In addition, workload is also proven to have a positive and significant effect on job stress. Job stress also significantly affects burnout. Most importantly, this study proves that job stress significantly mediates the relationship between workload and burnout. This means that a high workload will increase stress levels, ultimately leading to burnout in employees. The practical implication of this research is the need for PT. PLN (Persero) UP3 Malang to focus not only on workload management but also on developing effective stress management strategies. Theoretically, this research contributes to the development of the Job Demands-Resources model, particularly in clarifying the mediating role of job stress on burnout.